Marine sponges of the genus Stelletta as promising drug sources: chemical and biological aspects - Qihao Wu; Bastien Nay; Min Yang; Yeke Ni; Hong Wang; Ligong Yao; Xuwen Li (Elsevier, 2019)
Marine sponges of the genus Stelletta are well known as rich sources of diverse and complex biologically relevant natural products, including alkaloids, terpenoids, peptides, lipids, and steroids. Some of these metabolites, with novel structures and promising biological activities, have attracted a lot of attention from chemists seeking to perform their total synthesis in parallel to intensive biological studies towards new drug leads. In this review, we summarized the distribution of the chemically investigated Stelletta sponges, the isolation, synthesis and biological activities of their secondary metabolites, covering the literature from 1982 to early 2018. KEY WORDS: Marine natural products, Stelletta sponge, Isolation, Total synthesis, Biological activity, Marine drug leads